Fabrication and bending behavior of thermoplastic composite curved corrugated sandwich beam with interface enhancement. (December 2018) - Du, Bing; Chen, Liming; Tan, Jingyan; Zhou, Hao; Zhao, Yang; Wu, Wenjun; Li, Weiguo; Fang, Daining; Chen, Liliang
Highlights: Thermoplastic composite curved corrugated sandwich beams (CSB) are fabricated. Failure loads are predicted and failure maps are drawn. The responses of axial and circular CSBs under three-point-bending are compared. An interface enhancement method is implemented for curved axial CSB. After enhancement, the load-carrying ability was improved by 60%. Abstract: Thermoplastic composite sandwich structures are being widely investigated due to their excellent properties such as recycling feasibility and high damage tolerance to meet the increasing demand for lightweight engineering components. Three-point-bending (TPB) behavior of glass fiber reinforced polypropylene curved corrugated sandwich beams taking account of the effects of core configuration and interface property were analytically and experimentally investigated. Analytical models were developed to predict the failure loads considering face sheet buckling/crushing, core buckling/crushing and core debonding. The curved axial corrugated sandwich beams (CACSB) and curved circular corrugated sandwich beams (CCCSB) were fabricated by hot-pressing and adhesive bonding. Interface enhancement was implemented by polypropylene glue stick insertion. Compared with unenhanced ones, the peak load of polypropylene glue stick reinforced (PPRGS) CACSB is 1.6 times and the maximum displacement before failure extends to 5.9 times. Failure maps were constructed to insight the failure modes of three configurations and also provide useful instruction for designing lightweight sandwich structures. Graphicalabstract : Image, graphical abstract